Graphene cantilever under Casimir force. (19th April 2018) - Derras-Chouk, Amel; Chudnovsky, Eugene M; Garanin, Dmitry A; Jaafar, Reem
Abstract: The stability of graphene cantilever under Casimir attraction to an underlying conductor is investigated. The dependence of the instability threshold on temperature and flexural rigidity is obtained. Analytical work is supplemented by numerical computation of the critical temperature above which the graphene cantilever irreversibly bends down and attaches to the conductor. The geometry of the attachment and exfoliation of the graphene sheet is discussed. It is argued that graphene cantilever can be an excellent tool for precision measurements of the Casimir force.